2017
DOI: 10.1590/abd1806-4841.20175561
|View full text |Cite
|
Sign up to set email alerts
|

Acute generalized exanthematous pustulosis induced by hydroxychloroquine: a case with atypical clinical presentation

Abstract: Acute generalized exanthematous pustulosis is a rare drug-induced eruption that is characterized by acute, nonfollicular sterile pustules on an erythematous and edematous base. The most frequently implicated drugs are beta-lactam antibiotics. Hydroxychloroquine has been widely used to treat dermatologic and rheumatologic diseases and has been reported as a rare cause of acute generalized exanthematous pustulosis. A 42-year-old female presented with pustular lesions on the skin surface with erythema, facial ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 11 publications
0
26
0
4
Order By: Relevance
“…Systemic corticosteroids are usually used for severe cases . Some authors have reported using dapsone and cyclosporine in treatment of severe and atypical forms of AGEP as case reports …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Systemic corticosteroids are usually used for severe cases . Some authors have reported using dapsone and cyclosporine in treatment of severe and atypical forms of AGEP as case reports …”
Section: Discussionmentioning
confidence: 99%
“…We also reviewed the literature in English since 2008 to 2018 and found nine other cases . The details of the cases are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(7,8). Bu yayınlarda ilaç başlandıktan 2-3 hafta içerisinde lezyonların geliştiği belirtilmiştir ve vakalardan 2 tanesi Türkiye'den bildirilmiştir (9,10).…”
Section: Olguunclassified